Validation of the Fusion Risk Score for Thoracic and Lumbar Spine Fusion Procedures. Issue 8 (October 2018) - Deogaonkar, Kedar; Mehbod, Amir A.; Dawson, John M.; Transfeldt, Ensor E.
Abstract : Study Design: This is a retrospective cohort study. Objective: This study aimed to determine whether the Fusion Risk Score (FRS) is valid for perioperative complications. Summary of Background Data: The FRS was previously formulated from a retrospective review of 364 fusion surgeries in patients over age 65. Patient demographics, comorbidities, surgical approach, levels, and osteotomies are incorporated in a weighted manner. This score correlated well with the risk of perioperative complications, operative time, estimated blood loss during surgery, and length of hospital stay. Materials and Methods: A new cohort of patients was studied. Subjects were 65 years old or older and had undergone routine elective thoracic or lumbar fusion surgery. The FRS was calculated for each subject to estimate risk (low, medium, or high) for perioperative complications. Actual incidences of major complications in the first 90 days after the surgery were noted and statistically compared with the predicted risk. The FRS was compared with intensive care unit admittance, estimated blood loss, operative time, and hospital length of stay to determine whether the score was predictive. Results: In total, 51% of our patients were at low risk (FRS, 1–3) for perioperative complications; 43% were at medium risk (FRS, 4–9); and 7% were at high risk (FRS, over 9). A total of 8% in the low-risk group, 23% in the medium-risk group, and 67% in the high-risk group actually developed significant perioperative complications. Medium-risk and high-risk patients experienced proportionally more perioperative complications than did low-risk patients; the difference was highly statistically significant. Conclusions: This study validated the association between the FRS and complications in the first 90 days after thoracolumbar spinal fusion surgery on the basis of patient and surgery characteristics. It also predicts the risk of intensive care unit admission, operative time, blood loss, and hospital length of stay.